Titanium Implant Corrosion and Peri-Implant Disease: Current Concepts and Future Directions - Ankita Nayyar; Anchal Sood; Swantika Chaudhry; Harsukhman Kaur; Chhavi Khanna; Priyanka Pawar (Oral Sphere Journal of Dental and Health Sciences, 2026)
Background: Successful endodontic treatment depends on comprehensive knowledge of root canal anatomy. However, complex canal configurations, especially in mandibular first molars, pose diagnostic and therapeutic challenges. One such anatomical variation is the middle mesial canal (mmc), situated between the mesiobuccal (mb) and mesiolingual (ml) canals. Often undetected in conventional radiographs due to its narrow, calcified nature, failure to identify and treat the MMC may result in persistent infection and treatment failure. Enhanced magnification and advanced diagnostic tools like CBCT and dental operating microscopes (dom) have improved the detection of such variations. Case Presentation: A 26-year-old female presented with deep caries and tenderness in the mandibular left first molar (tooth #36). Clinical and radiographic examination confirmed pulpal necrosis with symptomatic apical periodontitis. Following informed consent and isolation, an access cavity was prepared. Under DOM, an additional canal orifice identified as an MMC was located between the MB and ML canals. Following this, working lengths were confirmed, instrumentation was done, and obturation and post-endodontic restoration were completed. Conclusion: This case highlights the importance of careful access cavity preparation, the use of magnification, and ultrasonic instrumentation in detecting and managing middle mesial canals (MMCs). Modern endodontic tools such as the dental operating microscope and ultrasonic tips play a vital role in revealing these often-hidden anatomical variations, which are essential to clean and seal for long-term success. Missing such canals can compromise treatment outcomes. Therefore, clinicians should remain vigilant, especially when treating mandibular first molars, and take time to explore the pulpal floor for any additional canal openings thoroughly. Recognizing and addressing these variations early in treatment can significantly enhance the prognosis and longevity of endodontic therapy.